Analysis of legal building regulations in Kazakhstan and abroad - Omarova, A.T.; Mukanov, B.O.; Dauletbayeva, L.M. (Bulletin of the Karaganda University “Law Series”, 2025)
The article reviews a large volume of normative literature, and the considered concepts and terminology were applied to three international cases concerning building codes and rules for their application. The purpose of this study is to comprehensively analyze the legal aspects of the application of Eurocodes and international building standards in the construction industry of Kazakhstan, identify the degree of harmonization of national legislation with international standards, and assess their impact on ensuring the safety, quality and sustainability of construction projects, taking into account judicial practice and law enforcement. Improving the recommendations and implementing international building standards in the construction industry of Kazakhstan will improve the safety and quality of construction projects, ensure their compliance with the requirements of Eurocodes and other international standards, reduce the likelihood of accidents and violations of building regulations, minimize legal risks associated with non-compliance with design documentation. It will also help attract foreign investment by increasing confidence in the construction sector, accelerating the processes of integration into the global economic space and creating conditions for sustainable development of the construction industry in accordance with global trends and best practices. These aspects determine the relevance of this study. The methodological basis of the work includes the analysis of regulatory legal acts of the Republic of Kazakhstan and international standards in the construction sector, a comparative legal method for determining the differences and distinctions between Kazakhstani building codes and Eurocodes, statistical analysis of data on violations of building standards and their consequences, as well as analysis to determine the relationship between the quality of construction work and international building standards. The study uses a systematic approach for a comprehensive consideration of legal and technical aspects, including the collection and processing of data on the regions of Kazakhstan, identifying existing problems and developing practical recommendations. The result of the study is the identification of problems and specific proposals for improving additional legal guidelines for the phased quality of Eurocodes, state control over compliance with international standards and the preparation of programs for specialists in the construction industry, contributing to the sustainability and competitiveness of the construction sector of Kazakhstan.